In vitro cell stretching technology (IsoStretcher) as an approach to unravel Piezo1-mediated cardiac mechanotransduction. (January 2021) - Guo, Yang; Merten, Anna-Lena; Schöler, Ulrike; Yu, Ze-Yan; Cvetkovska, Jasmina; Fatkin, Diane; Feneley, Michael P.; Martinac, Boris; Friedrich, Oliver
Abstract: The transformation of electrical signals into mechanical action of the heart underlying blood circulation results in mechanical stimuli during active contraction or passive filling distention, which conversely modulate electrical signals. This feedback mechanism is known as cardiac mechano-electric coupling (MEC). The cardiac MEC involves complex activation of mechanical biosensors initiating short-term and long-term effects through Ca 2+ signals in cardiomyocytes in acute and chronic pressure overload scenarios (e.g. cardiac hypertrophy). Although it is largely still unknown how mechanical forces alter cardiac function at the molecular level, mechanosensitive channels, including the recently discovered family of Piezo channels, have been thought to play a major role in the cardiac MEC and are also suspected to contribute to development of cardiac hypertrophy and heart failure. The earliest reports of mechanosensitive channel activity recognized that their gating could be controlled by membrane stretch. In this article, we provide an overview of the stretch devices, which have been employed for studies of the effects of mechanical stimuli on muscle and heart cells. We also describe novel experiments examining the activity of Piezo1 channels under multiaxial stretch applied using polydimethylsiloxane (PDMS) stretch chambers and IsoStretcher technology to achieve isotropic stretching stimulation to cultured HL-1 cardiac muscle cells which express an appreciable amount of Piezo1.